Проблеми збереження різноманітності рослин ex situ - Cherevchenko, Т.M.; Moroz, P.A.; Kuznetsov, S.I.; Muzychuk, G.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
The principle of the complex gene-pool protection of the wild and cultivated flora in botanical gardens in combination with the seed storage in gene banks was assumed as a basis of plant diversity conservation problems decision. The most important program component parts of plant diversity conservation ex situ as well as the arrangements for this program realization in Ukraine were determined. Basic directions of scientific investigation with the purpose of growing rare and vanishing plants in botanical gardens and dendroparks, including their repatriation in natural phytocenoses were also defined.